Principles of transplantation: overview of the immune response - Wood, Kathryn (Henry Stewart Talks, 2021)
Organ Transplantation, Immunology, Definitions of Organ Transplantation, Major Histocompatibility Complex, Graft vs. Host Disease, Tissue Typing, Crossmatching, Graft Injury, Bone Marrow Transplantation, Hematopoietic Stem Cell Transplantation
Reviewed at 2025/01/29